Evaluation and mechanism of interaction effect between thermoplastic polyurethane elastomer modified asphalt and fillers. Issue 40 (19th August 2022) - Jin, Xin; Wang, Fengchi; Yang, Yanhai; Guo, Naisheng; Zhang, Huaizhi; Liu, He
Abstract: Thermoplastic polyurethane (TPU) elastomer modified asphalt mastic is regarded as a two‐phase composite composed of TPU modified asphalt and filler according to the micro‐mechanics theory of composites, and its rheological properties are affected by various types of asphalt, mineral filler, and dosage. In this study, different kinds of fillers (limestone, granite, fly‐ash, coal gangue) and TPU modified asphalt (grade of base asphalt labeled as 90# and polyether‐based TPU modified asphalt with C h  = 40, r  = 1.05 through a self‐determined laboratory process) were prepared into asphalt mastic. The dynamic shear rheology and bending beam rheology (BBR) were used to test and evaluate the high and low temperature rheological properties of TPU modified asphalt mastic with different kinds of fillers. The scanning electron microscopy, atomic force microscopy, Brunauer, Emmett, and Teller method, X‐ray diffraction, Fourier transform infrared spectroscopy, and other tests were used to analyze the interaction mechanism between fillers and TPU modified asphalt. The results indicated that the enhancement coefficients λ ¯ H and λ ¯ L of different fillers are obtained based on the | G *| and S master curve, and the optimum ratio range in TPU modified asphalt with different kinds of fillers are from 1.04 to 1.41. The interaction parameters Luis Ibrarra‐ A ( A ‐values) and Palierne‐ C ( C ‐values) were obviously better than K. Ziegel‐ B ( B ‐values) and Complex shear modulus coefficient ( Δ G * ‐values). The surface of coal gangue was rough and emerged micro‐void, the BET specific surface area reached 2.681 m 2 /g, which was the largest than the other fillers, and the interaction with TPU modified asphalt was the strongest due to the C ‐value is 1.562. The chemical composition of coal gangue played an important role in the interaction with asphalt. Physical adsorption is the main mechanism between TPU modified asphalt and fillers. The absorption peak of the original TPU modified asphalt disappeared at 3343 cm −1, and more CaO and Al2 O3 in coal gangue are helpful to improve the interaction ability with TPU modified asphalt. There is a significant correlation between the number and area ratio of "bee‐like structure" in TPU modified asphalt mastic and interaction coefficient C ‐values. Abstract : The structural asphalt and free asphalt can affect the macroscopic mechanical properties of asphalt mastic. Hence, TPU modified asphalt mastic can be regard as a two‐phase composite material composed of TPU modified asphalt and filler. Its rheological characteristics and internal mechanism are affected by TPU modified asphalt and different kind of fillers.